Development of Early Childhood Gender Identity Flashcards; Prevention of Gender Dysphoria of Islamic Generation - Raja Ahmad, Raja Rahima Munawarah; Suryani, Lilis; Mansor, Norwati Binti; Devianti, Rika; Hasgimianti, Hasgimianti (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2025)
This research aims to test the feasibility of gender identity flashcards based on Islamic teachings for early childhood. Various developments of flashcards for early childhood have been developed, but flashcards about gender identity have not received much attention. The research was located in Pekanbaru City, the research subjects were 37 young children. This research has used an RD approach. Data has been collected using interviews and Likert model questionnaires. Data has been analyzed using percentages and categorization. The results of this research have shown that the gender identity flashcard media is very suitable to be used as a learning medium to introduce gender identity according to Islamic teachings in early childhood based on the results of the combined validity test (89.04%). The results showed that these flashcards are suitable for use in early childhood learning to recognize gender identity according to Islamic teachings, to prevent gender dysphoria. This research can be used by early childhood education teachers and guidance and counseling teachers in designing lessons containing gender recognition for children.